NF‐κB signaling regulates the generation of intermediate progenitors in the developing neocortex. (3rd August 2015) - Yamanishi, Emiko; Yoon, Keejung; Alberi, Lavinia; Gaiano, Nicholas; Mizutani, Ken‐ichi
<x xml:space="preserve">Abstract</x> In addition to its well‐established role during immune system function, NF‐κB regulates cell survival and synaptic plasticity in the mature nervous system. Here, we show that during mouse brain development, NF‐κB activity is present in the neocortical ventricular and subventricular zones (VZ and SVZ), where it regulates proliferative pool maintenance. Activation of NF‐κB signaling, by expression of p65 or an activated form of the IκB kinase complex subunit IKK2, inhibited neuronal differentiation and promoted retention of progenitors in the VZ and SVZ. In contrast, blockade of the pathway with dominant negative forms of IKK2 and IκBα promoted neuronal differentiation both in vivo and in vitro. Furthermore, by modulating both the NF‐κB and Notch pathways, we show that in the absence of canonical Notch activity, after knockdown of the pathway effector CBF1, NF‐κB signaling promoted Tbr2 expression and intermediate neural progenitor fate. Interestingly, however, activation of NF‐κB in vivo, with canonical Notch signaling intact, promoted expression of the radial glial marker Pax6. This work identifies NF‐κB signaling as a regulator of neocortical neurogenesis and suggests that the pathway plays roles in both the VZ and SVZ.